Perbandingan Bahan Basis Resin Akrilik Kovensional dengan Bahan Basis Fleksibel Nylon Termoplastik pada Gigi Tiruan Sebagian Lepasan (Literature Review) - Dyah Ayu Cahyaningrum; Retnosari Retnosari (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
Partial Denture (GTSL) is an ideal option for patients with missing teeth, with various materials such as thermoplastic nylon (flexible denture), acrylic resin, and metal. Heat-cured acrylic resin and thermoplastic nylon are the two most commonly used materials for denture bases. Denture bases must have sufficient mechanical strength to withstand chewing forces. Acrylic resin, made from polymethyl methacrylate, has become the gold standard in prosthodontics due to its affordability, ease of fabrication, and satisfactory functional results. However, acrylic resin tends to be rigid, brittle, and may cause soft tissue irritation. As an alternative, thermoplastic nylon offers high physical strength, resistance to heat and chemicals, as well as plastic and flexible properties. However, thermoplastic nylon tends to absorb water, change color, and is difficult to repair. Thermoplastic nylon-based dentures provide comfort, aesthetics, and good marginal adaptation, with less soft tissue irritation compared to acrylic resin dentures. Although both materials have comparable characteristics in terms of retention, stability, and durability, flexible dentures are more attractive to patients who prioritize comfort and aesthetics.